(untitled) (Indian Journal of Child Health, 2022)
Introduction: Asthma is a common chronic disease in childhood and has been subject of studies for at least two decades, due to its increasing prevalence. The symptoms are persistent, recurrent, and entirely related to bronchial hyper-responsiveness to many environmental triggers. Nebulization and metered dose inhaler (MDI) are two available modalities of salbutamol administration in patients with acute asthmatic attack. Aim: The aim of the study was to compare the relative efficacy of nebulizer and MDI with spacer for the administration of salbutamol in the treatment of acute asthmatic attack. Materials and Methods: A randomized, prospective, and interventional study was conducted on 100 children aged 1–12 years with acute asthmatic attack at a tertiary care. The subjects were randomized into two groups for salbutamol administration. Group I was given salbutamol by nebulizer and Group II by MDI with spacer. Demographic data and detailed history was collected. Children were categorized into mild, moderate, and severe grade according to peak expiratory flow rate (PEFR) and pulmonary index (PI) score. Oxygen saturation, PEFR, and PI were monitored at 0, 20, 40, and 60 min of therapy. Other details such as duration of hospital stay and oxygen requirement were also noted. Results: One hundred children with male female ratio of 1.12:1 were included in the study. Highest incidence was seen in age group of 1–3 years (38%). Statistically significant change in PI and PEFR was noted with treatment in both the groups (p<0.05). On comparison between MDI and nebulizer group, no statistically significant difference was found (p>0.05). Conclusion: MDI with spacer is an effective alternative to nebulizer for the administration of salbutamol drug in acute asthmatic attack in pediatric patients.